Third Five Year Plan Kerala State Materials relating to Outlays, Targets and Programmes for the Final Report - Planning Commission (Planning Commission)
Establishment of Seed Farms and Seed Stores.—It has been estimated that about 800 acres of paddy lands are required for growing sufficient quantities of foundation seeds of improved varieties. The area that has been brought under seed farms till the end of the Second Plan is 300 acres. The additional area of 500 acres will be brought under seed farms during the Third Five Year Plan. Seed Stores will be established for storing improved seeds, implements and other agricultural requisites at block level for distribution to cultivators.
Kerala State